2020
DOI: 10.3389/fgene.2020.00911
|View full text |Cite
|
Sign up to set email alerts
|

Complex Mosaicism of Two Distinct Mutations in a Female Patient With KCNA2-Related Encephalopathy: A Case Report

Abstract: KCNA2 gene mutations were described to cause a new molecular entity within the developmental and epileptic or epileptic encephalopathies. Here, we firstly reported a patient with an unusual mosaicism for KCNA2, presenting two distinct mosaic missense mutations at the same loci. Clinical trio-based whole-exome sequencing using next-generation sequencing (NGS) revealed two novel mutations in KCNA2: c.1225A > T [p.(Ile409Phe)] and c.1225A > C [p.(Ile409Leu)]. Both missense mutations were in mosaic status and Sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Interestingly, an unusual case of mosaicism of two novel missense variants in KCNA2 had been reported, expanding the phenotypic spectrum associated with this mutations of gene, but not presenting with myoclonic epilepsy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an unusual case of mosaicism of two novel missense variants in KCNA2 had been reported, expanding the phenotypic spectrum associated with this mutations of gene, but not presenting with myoclonic epilepsy (23).…”
Section: Discussionmentioning
confidence: 99%
“…For GOF variants, clinical trials of 4‐aminopyridine (an approved K + blocker) in patients with GOF mutations have been reported 2 . In China, Gong et al 25 reported an epilepsy patient with an unusual mosaicism for KCNA2 and found that the combination of valproic acid (VPA) and levetiracetam (LEV) may be effective for epilepsy caused by KCNA2 loss‐of‐function mutation.…”
Section: Kcna2 In Epilepsymentioning
confidence: 99%
“…KCNA2 is a DEE-associated gene that encodes the voltage-gated K+ channel KV1.2 [ 76 ]. For instance, Gong et al [ 80 ] reported the first known patient with mosaicism in KCNA2, who had two different mosaic mutation alleles at the same nucleotide in KCNA2: c.1225A>T and c.1225A>C. However, it remains unclear whether complex mosaicism is a contributor to the clinical underdiagnosis of KCNA2-related encephalopathy.…”
Section: Application Of Next-generation Sequencing In Neurogenetic Diseasesmentioning
confidence: 99%